Inhomogeneous α-Al/Mg2Si two-phase microstructures with chemical fluctuation produced by laser-beam powder bed fusion - Yuki Otani; Naoki Takata; Asuka Suzuki; Makoto Kobashi; Junji Umeda (Materials & Design)
This study investigated the additive manufacturing of high-strength Al–Mg–Si ternary alloy with refined α-Al/Mg2Si two-phase microstructures by laser-beam powder bed fusion (PBF-LB). Although PBF-LB processing produced crack-free samples with high relative densities (>99.5 %), the scanning laser irradiation caused significant Mg vaporization, reducing the Mg content of the sample from 11.3 to 7.6 %. Laser-induced vaporization caused micron-scale chemical fluctuations in the melt-pool structure, resulting in the development of inhomogeneous microstructures. Refined cellular microstructures with many columnar α-Al phases surrounded by numerous Mg2Si nano-particles were observed in most parts of the melt-pool structure, corresponding to hypo-eutectic compositions in the Al–Mg–Si ternary system. However, primary solidified Mg2Si phases were observed in some parts of the melt-pool boundaries with local Mg-rich compositions (hyper-eutectic compositions). The PBF-LB manufactured alloy specimens with a total composition of Al–7.6Mg–5.4Si (wt%) exhibited a high tensile strength, which reduced significantly with increasing testing temperature, and low ductility (529 MPa and < 2 %, respectively) at room temperature. Moreover, the specimens underwent mechanical deterioration at elevated temperatures, owing to a significant coarsening of metastable microstructural factors (nanoscale Mg2Si precipitates or their related metastable phases and atomistic clusters) that contribute towards the high room-temperature strength.